Ischemia-modified albumin as a novel marker for diagnosis of necrotizing enterocolitis in newborn infants - Safaa ELMeneza; Asmaa Okasha; Manal Abd El-Hafez; Naeema Hussein (Hygeia Press di Corridori Marinella, 2021)
Background: Necrotizing enterocolitis (NEC) is the most common neonatal gastrointestinal emergency. Ischemia-modified albumin (IMA) is a marker of oxidative stress and ischemia. Its role in early diagnosis of NEC has been little investigated so far. Aim: The objective of our research was to study the role of serum IMA in diagnosis of NEC in newborn infants. Material and methods: The study was carried out on 80 neonates; 40 with NEC and 40 controls, subjected to serum IMA dosage with ELISA. Results: There was a highly statistically significant increase in IMA in both preterm (60.59 ± 34.97 U/ml) and full-term infants with NEC (60.50 ± 29.88 U/ml) compared to their controls (11.28 ± 3.09 U/ml; 5.34 ± 1.88 U/ml). The positive predictive value of IMA in preterm and full-term with NEC was 100% and 94.74%, while the negative predictive value was 80% and 90.48%, respectively. There was a statistically significant increase in serum level of IMA in stage II NEC compared to stage I NEC as well as in non-survivor cases. Significant positive correlation between serum IMA level and duration of recovery from NEC was detected. Conclusions: IMA is a sensitive marker for diagnosis of NEC in full-term and preterm infants and can predict severity of NEC and death.